Allobaculum Involves in the Modulation of Intestinal ANGPTLT4 Expression in Mice Treated by High-Fat Diet - Zheng, Zibin; Lyu, Wentao; Ren, Ying; Li, Xiaoqiong; Zhao, Shenjun; Yang, Hua; Xiao, Yingping (Frontiers in Nutrition, 2021)
Increasingly studies have shown that obesity is the primary cause of cardiovascular disease, nonalcoholic fatty liver disease, type 2 diabetes, and a variety of cancers. The composition of gut microbiota is one of the main causes of obesity. Meanwhile, Recent research indicated ANGPTL4 was a circulating medium for gut microbiota and fat deposition in the body. The study was conducted to investigate the alteration of gut microbiota and intestinal ANGPTLT4 expression in mice by high-fat diet treatment. Twenty C57BL/6J mice were randomly allocated to two groups and fed high-fat diet (HFD) with 60% fat or normal-fat diet (Control) with 10% fat. The relative expression of ANGPTL4 in the ileum and colon was measured by qPCR, mice ileal and colonic tissues were taken for immunohistochemical analysis. The result showed that mice fed HFD exhibited increased body weight, liver weight, epididymal fat, perirenal fat, and the lipid contents in the liver. We also found that the relative expression of ANGPTL4 and the ANGPTL4-positive cells in the ileum and colon of mice was significantly increased after a high-fat diet. Furthermore, 16S rRNA gene sequencing of the ileal and colonic microbiota suggested that HFD changed the composition of the gut microbiota. Interestingly, the abundance of Allobaculum increased significantly by HDF treatment and positively correlated with the expression of ANGPTL4. Our findings provide a reference for the future research on the regulation of ANGPTL4 by gut microbiota in the intervention of obesity.